Highly Luminescent 4′‐(4‐ethynylphenyl)‐2, 2':6', 2''‐Terpyridine Derivatives as Materials for Potential Applications in Organic Light Emitting Diodes. Issue 27 (21st September 2017) - Zych, Dawid; Slodek, Aneta; Matussek, Marek; Filapek, Michał; Szafraniec‐Gorol, Grażyna; Krompiec, Stanisław; Kotowicz, Sonia; Siwy, Mariola; Schab‐Balcerzak, Ewa; Bednarczyk, Katarzyna; Libera, Marcin; Smolarek, Karolina; et al.
Abstract: Four novel derivatives of 4'‐(4‐ethynylphenyl)‐2, 2':6', 2''‐terpyridine with 7‐(N, N‐diphenylamino)‐9, 9‐dioctylfluorene, 7‐(9 H ‐carbazo‐9‐yl)‐9, 9‐dioctylfluorene, 9‐octyl‐9 H ‐carbazole, 6‐(9 H ‐carbazo‐9‐yl)‐9‐octylcarbazole substituents were obtained via Sonogashira cross‐coupling reaction and thoroughly characterized. DSC measurements demonstrated that prepared terpyridine derivatives are molecular glasses, which exhibited high thermal stability based on TGA analysis. Since they showed high photoluminescence (PL) quantum yields approaching 80% in solution, the electroluminescence ability of the compounds was tested in diodes in a guest‐host configuration. Upon dispersing in a matrix consisting of poly(9‐vinylcarbazole) (PVK) (50 wt %) and (2‐tert‐butylphenyl‐5‐biphenyl‐1, 3, 4‐oxadiazole) (PBD) (50 wt %), PL radiation with quantum yields in the range of 22–58% with maximum of emission band from 369 to 459 nm was observed, and the devices showed green or red electroluminescence. The results of the underline substantial role of the functional groups and the linker in the presented terpyridines in terms of their thermal, electrochemical, optical and electroluminescence properties. In addition, density functional theory (DFT) and time‐dependent‐density functional theory (TD‐DFT) calculations were performed to provide a deeper understanding of the experimental results. Abstract : Novel soluble derivatives of 4'‐(4‐ethynylphenyl)‐2, 2':6', 2''‐terpyridine are developed, synthesized and thoroughly characterized. New molecules are molecular glasses with high thermal stability and efficient luminophores with high photoluminescence quantum yield approaching 80%. The electroluminescence of all compounds is tested in diodes in a guest‐host configuration. They present PL radiation with Φ in the range of 22–58% with a maximum of emission band from 369 to 459 nm. Obtained data are supported by the theoretical study.